Fire safety requirements for building integrated photovoltaics (BIPV): A cross-country comparison. (March 2023) - Yang, Rebecca; Zang, Yukun; Yang, Jiaqi; Wakefield, Ron; Nguyen, Kate; Shi, Long; Trigunarsyah, Bambang; Parolini, Fabio; Bonomo, Pierluigi; Frontini, Francesco; Qi, Dahai; Ko, Yoon; et al.
Abstract: Building-integrated photovoltaics (BIPV), which can be integrated into the surface of a building (roof or facade), replacing conventional building materials, offer significant contributions to the achievement of net-zero energy buildings. However, fire safety is of vital concern in using BIPV as a construction system in buildings, and it is essential that the application of BIPV as building facades and roofs does not adversely affect the safety of construction products, building occupants and firefighters. As multifunctional products, BIPV modules must satisfy the fire safety requirements of both electrical and building-related sectors. This paper provides a comparison of normative frameworks applicable to BIPV modules in different countries. The comparisons show that IEC 61215 and IEC 61730 are the PV standards used in almost all countries, while the USA and Canada comply with UL1703. Regarding building regulations, the fire safety requirements of BIPV must comply with national/local building regulations. In the countries investigated, each country has fire regulations to guide the fire performance of building elements to which BIPV modules could be applied, including external walls, roofs/skylights, windows and other openings, and ancillary elements/attachments. This report also points out future research directions which would help develop BIPV fire prevention strategies globally. The review of regulations and standards in this paper makes a contribution to the clarification of the performance requirements of fire safety for BIPVs in the investigated countries for BIPVs, which remain barrier to the development of BIPV around the world. Furthermore, the future research directions suggested in this paper will inspire further research in this field. Graphical abstract: Image 1 Highlights: BIPV fire hazards include ignition, fire propagation, and hazards to building occupants and rescue operations. The electrical fire safety requirements of PV modules are based on the same international standards. The studied countries have different fire safety requirements for building elements.